Assessing fishery interaction on cetaceans stranded along the Italian coastline between 1986 and 2023 - Guido Pietroluongo; Michela Podestà; Donatella Belluscio; Enrica Berio; Cristina Canonico; Cristina Casalone; Federica Cavaliere; Cinzia Centelleghe; Luca Ceolotto; Cristiano Cocumelli; Bruno Cozzi; Daniele Denurra; et al. (PLoS ONE, 2025)
Monitoring stranded cetaceans represents a strategic method to assess their health, conservation status, and ecological role in the marine ecosystem. Efficient stranding networks and standardized protocols are essential to monitor this phenomenon and investigate its causes. This study assesses the evidence of fishery interaction on stranded cetacean carcasses found along the Italian coastline from 1986 to 2023. Evidence assessment and post-mortem investigation methods evolved over three macro-periods, from non-standardized reporting (1986–2014) to an integrated national stranding network (2015–2019), and finally to the creation of a new standardized, evidence-based diagnostic framework under the EU-funded LIFE DELFI project (LIFE18 NAT/IT/000942) (2020–2023). A total of 5355 cases were selected for this analysis. A literature review and evidence of interaction on stranded carcasses supported the categorization of findings, ranging from case history to pathological observations, allowing the assessment of temporal variation, demographic parameters, geographical distribution, and fishing gear identification. Evidence of fishery interaction was found in 12.89% of the cases (690/5355), with an annual average of 18.15 affected animals, and fishery interaction was identified as the likely cause of death in 10.32% of the cases. The most frequently reported species were Stenella coeruleoalba and Tursiops truncatus, showing significant differences in fishery interactions, particularly in relation to sex, age class, and geographical distribution. Adult male Tursiops truncatus exhibited a higher susceptibility to gillnet interaction in the Adriatic Sea. The results of this study emphasize the importance of standardized post-mortem investigations and long-term monitoring to identify risk hotspots, implement species- and region-specific mitigation strategies, and establish threshold values for cetacean conservation.